Customers' awareness and perceptions toward safe deposit box services provided by Alliance Bank Satok Branch / Alice Stephen Sundin - Stephen Sundin, Alice (2002)
The banking industry has become more and more competitive nowadays. The bank does not only have to compete among themselves but also with non banks competitors. The customers are also becoming more and more demanding each day. Thus, the bank must be prepared to meet their expectations by offering high service quality to its customers. Realizing the importance of quality service, a study was carried out in order to assess the customers' awareness and perceptions toward the Safe Deposit Box services provided by Alliance Bank Satok Branch at Jalan Kulas, Kuching. Based on the questionnaires distributed to the respondents of Alliance Bank Satok Branch, 84% of the respondents are aware of the Safe Deposit Box services provided by this bank. However, the number of respondents who maintain a Safe Deposit Box with the branch is only 52% of the total number of respondents who are actually aware of the availability of Safe Deposit Box services. Most respondents who do not maintain any Safe Deposit Box with the branch explained that they have no valuable things to put in the Safe Deposit Box.